More than Just Great Quotes: An Introduction to the Canadian Tri-Council’s Qualitative Requirements - Jody Boffa; Nancy Moules; Maria Mayan; Robert L Cowie (Canadian Journal of Infectious Diseases and Medical Microbiology)
Although at times misunderstood by the general research community, qualitative research has developed out of diverse, rich and complex philosophical traditions and theoretical paradigms. In the most recent Canadian Tri-Council policy statement on the ethical conduct of research involving humans, a chapter was devoted to a summary of methods and methodological requirements that characterize robust qualitative research, despite the diversity of approaches. To dispel common misperceptions about qualitative research and introduce the unfamiliar reader to these requirements, the work of a qualitative study on isoniazid preventive therapy for prophylaxis of tuberculosis published in AIDS is critiqued alongside each of the Tri-Council’s nine requirements.